UTILIZATION OF DIGITAL MEDIA IN MARKETING GAYO ARABICA COFFEE - Sinta, Irada; Nur Ilham, Rico; Authar ND, Muhammad; M. Subhan; Amru Usman (RADJA PUBLIKA, 2022)
The opportunity for the coffee industry in Indonesia is very good, especially with the increasing recognition of Indonesian coffee in Europe and America, especially specialty coffees such as Gayo coffee. Arabica coffee production centers in 2015-2018 are in the provinces of Aceh, North Sumatra, South Sulawesi, West Sumatra, and West Java. Aceh is one of the largest coffee producing regions in Indonesia. There are six districts that are centers of coffee production in Aceh Province. Central Aceh District and Bener Meriah District are the main production centers among the six districts. Product marketing that is quite effective during a pandemic is an activity that avoids direct face-to-face with the use of digital media as a communication medium, such as in the form of video marketing. Currently, digital communication media is an effective and efficient choice to market Gayo Arabica coffee. Technological advances have also changed the pattern of communication and product information search by consumers through digital media, many businesses are growing because of the availability of supporting technology. The use of technology that is currently a trend is one of the uses of digital media. The evolution of marketing strategies through content on digital media such as websites and other social media is a new way to get customers and reach targets. This activity aims to provide knowledge about marketing strategies through digital media, as a reference for future community service activities. The activity was carried out in Central Aceh District.